European Duties of Social Justice: A Kantian Framework. (6th January 2019) - Claassen, R.J.G. (Rutger)
Abstract: This contribution asks how to approach the question of whether the European Union should – replacing or supplementing member states – also be a locus of social justice‐based duties to provide welfare state services. The contribution scrutinizes two important theories of global justice (cosmopolitan and relational theories) and finds that their normative assumptions hinder them from adequately addressing this question. A new theory is proposed, inspired by Immanuel Kant's political philosophy. The core idea is that social justice requires public authorities to protect citizens against private forms of coercion; and that the level (national, European, global) at which such authority needs to be exercised depends on which arrangement best protects citizens' rights to independence. The paper outlines several duties of global justice to give specificity to this general principle, and then applies them to the case of integrating European welfare states.